Traditional uses and ecological resemblance of medicinal plants in two districts of the Western Aegean Region (Turkey) - Guler, Behlul; Erkan, Yildiz; Uğurlu, Emin (Springer, 2020)
We interviewed 91 people who use plants for medicinal purposes regularly in Altinova (Balikesir) and Kozak (Izmir) during 2009-2010. We recorded the local names of plants, useful parts of plants, ailments treated, preparation and application methods during the interviews. We performed a use value (UV) calculation to assess the relative importance of local species. We carried out informant consensus factor (F-IC) analysis to find out the level of disease homogeneity. Finally, we identified 63 plant taxa belonging to 32 families. Among these were 47 wild and 16 cultivated. Lamiaceae (14.3%), Asteraceae (12.7%), Rosaceae (9.5%), Chenopodiaceae (6.3%) and Brassicaceae (4.8%) families were the most common. Use values showed Urtica dioica L. and Malva sylvestris L. were the most commonly used species. Homogeneity of diseases (F-IC) values were the highest for dermatological, gastrointestinal and blood disorders, 0.93, 0.92 and 0.91, respectively. In our study, herb medicinal species showed more ecological differences than shrub and tree species in terms of altitudinal range and flowering period. Our results also showed that herbal remedies are substantially important among the local people.
Keywords: Ethnobotany; Ethnomedicine; Traditional medicine; Turkey